Cicero, Voltaire and the Bible: French Best-Sellers in the Age of Enlightenment?* - Burrows, Simon (Knygotyra, 2022)
Since the early twentieth century, when Daniel Mornet conducted his path-breaking survey of private library catalogues in an attempt to determine what people read during the enlightenment, historians have debated how to identify the best-selling texts in the distant past. Besides library catalogues, scholars of eighteenth-century France have ransacked will inventories, publishers’ archives, print licence registers, book auction records, the titles available in cabinets de lecture, and even the extraordinarily rich records of books stamped in an amnesty for pirated editions in 1777–1781. This article suggests that none of these sources taken in isolation can give us sufficient insight to provide a reliable overview of the book trade and the market for books. Taken together and analysed digitally, however, they give important representative insights into the best-selling texts, genres and authors of the eighteenth century. The article compares and contrasts the findings of several large-scale digital projects to identify and explore the best-selling – or most frequently-encountered-texts across a number of genres including school-books, self-help manuals, popular medical texts, creative literature and religious works. In the process, it will help us to think more critically about what constituted a best-seller in the early modern period. By revealing some broad contours of eighteenth-century print culture, it will also challenge existing narratives of the enlightenment, secularisation, popular literacy and the book trade.